On the Limit Distribution of Integrals of Shot-Noise Processes - Il'enko, A. B. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We establish limit theorems for integrals of shot-noise processes and study the asymptotic behavior of the moments of integrals of this type.